Circuit Training Training Assistance for Madiun City Science Society Tutoring Students - Agung Dwi Darmawan; Roy Try Putra; Ghon Lisdiantoro; Lukas Susanto (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2023)
Today's physical condition literacy is still rarely known by Gen-Z. Many people think that being healthy means being fit. Physical performance is now a necessity that cannot be separated from daily activities. Preparation to achieve prime physical condition is not achieved in a short time. Many methods are used to achieve excellent physical quality. Start with good physical exercise, meet balanced nutritional needs, stress management, and adequate hydration. There are many training methods to improve physical condition, one of which is the circuit training method. Circuit training can be done alone or in groups. There are many benefits to be gained if this circuit training exercise is carried out in groups, one of which is being able to increase the enthusiasm of students to carry out and complete the posts provided by the team coach. There are many phenomena that occur due to a lack of understanding of literacy about Circuit training exercises for science society tutoring students. So it is necessary to carry out assistance by carrying out community service whose aim is to provide literacy education for Circuit training exercises. Methods and forms of community service implementation using a participatory approach. The result of this assistance is the increasing understanding of the physical literacy of circuit training participants